PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 12 SMAN 11 SEMARANG - Divya Fitriyani; Testiana Deni Wijayatiningsih; Erna Setyawati (Journal of Lesson Study in Teacher Education, 2025)
This study aims to improve the learning outcomes of 12th-grade students of SMAN 11 Semarang through the application of the Think-Pair-Share (TPS) cooperative learning model. TPS was chosen for its ability to encourage critical thinking, effective communication, collaboration, and confidence building. This classroom action research (CAR) was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. Data collection included pretest and posttest scores, student activity observations, and documentation. The results showed significant improvements in students' learning outcomes, both cognitively and in 21st-century skills. In Cycle 1, the average pretest score was 48.19, increasing to 66.53 in the posttest, with a completion rate of 52.78%. In Cycle 2, the pretest average rose to 57.92, and the posttest average reached 78.75, with a completion rate of 66.67%. Additionally, the TPS model enhanced critical thinking, communication skills, student collaboration, and confidence. Observations indicated increased student engagement in questioning, sharing ideas, and participating in group discussions. The study concludes that the TPS model significantly improves academic learning outcomes and supports the development of essential 21st-century skills. Teachers are encouraged to adopt TPS as an alternative learning strategy in various subjects. Schools can support this model's success by providing training and resources, while universities are expected to prepare future educators to understand and implement innovative teaching strategies like TPS.